1998
DOI: 10.1016/s0014-5793(98)01384-2
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal expression of fractalkine in the presence and absence of inflammation

Abstract: Fractalkine is the only as yet known member of a novel class of chemokines. Besides its novel Cys-X-X-X-Cys motif, fractalkine exhibits features which have not been described for any other member of the chemokine family, including its unusual size (397 amino acids human, 395 mouse) and the possession of a transmembrane anchor, from which a soluble form may be released by extracellular cleavage. This report demonstrates the abundant mRNA and fractalkine protein expression in neuronal cells. The neuronal express… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
57
1
3

Year Published

1999
1999
2016
2016

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 102 publications
(72 citation statements)
references
References 17 publications
11
57
1
3
Order By: Relevance
“…This is in line with our previously published observations that the level of C1q biosynthesis monitored by Northern blot, in situ hybridization, and immunocytochemistry 1) is low and is restricted to microglial cells in normal rat and mouse brain and 2) is strongly up-regulated in CNS microglia after viral infection and experimental allergic encephalitis (27,34,38). We found that constitutive and lesion-induced C1q biosynthesis was absent in any brain-resident cells other than cells of the microglia/ macrophage lineage.…”
Section: Discussionsupporting
confidence: 91%
“…This is in line with our previously published observations that the level of C1q biosynthesis monitored by Northern blot, in situ hybridization, and immunocytochemistry 1) is low and is restricted to microglial cells in normal rat and mouse brain and 2) is strongly up-regulated in CNS microglia after viral infection and experimental allergic encephalitis (27,34,38). We found that constitutive and lesion-induced C1q biosynthesis was absent in any brain-resident cells other than cells of the microglia/ macrophage lineage.…”
Section: Discussionsupporting
confidence: 91%
“…High levels of expression of Fk and CX 3 CR1 have been reported in the CNS (6,9,29), and evidence for a functional role in glomerulonephritis has also been reported (10,25). In addition, there is emerging evidence that selected chemokines and their receptors are present and play an important role in transplant rejection (30).…”
Section: Discussionmentioning
confidence: 99%
“…However, these authors also reported that microglia were the principal fractalkine-expressing cells of the central nervous system. More recently, we and others have determined using in situ hybridization and immunohistochemical analysis that neurons are the principal fractalkine-expressing cells in the central nervous system (CNS) [24,27,28]. In support of the presence of fractalkine in endothelial cells, the expression of this chemokine has been demonstrated in cultured endothelial cells after their treatment with either interleukin-1 (IL-1) or tumor necrosis factor ␣ (TNF-␣) [21,23].…”
Section: Introductionmentioning
confidence: 98%